THE EFFECT OF BRAND EQUITY, PRICE, AND LIFESTYLE ON PRODUCT PURCHASE DECISIONS GATSBY POMADE IN CIRCLESMILLENNIAL IN THE CITY OF BANGKINANG - Rian Yunaldi; Litra Diantara; Librina Tria Putri (Jurnal Riset Manajemen Indonesia, 2021)
This study aims to determine whether the effect of brand equity price and lifestyle on purchasing decisions for Gatsby pomade products in Bangkinang City which was carried out for 2 months from August to September 2020. The analysis in this study used multiple linear analysis with 99 respondents. Sampling using the census method, namely the entire population is sampled and the hypothesis testing in this study uses the F test and T test. Based on the results of the study it can be concluded that simultaneously and partially Brand Equity Price and Lifestyle affect the purchasing decision of Gatsby pomade products in Bangkinang city. There is a strong positive relationship between the variables Brand Equity Price and Lifestyle on the purchase decision of Gatsby Pom with the contribution of the independent variable to the dependent variable of 61.10% while the remaining 38.90% is determined by other variables outside of this study.